Religious Practices of the Batubara Community Through Local Wisdom Traditions: Perspectives from Surah Al-Baqarah 165 - Said, Dede Hafirman; Vito Dasrianto; Elva Mahmudi (Medina-te : Jurnal Studi Islam, 2025)
This study aims to generate theoretical ideas about religious practices within the tradition of local wisdom. The fact that the Malay Batubara community continues to perform a healing ritual known as ubat-ubat serves as the foundation of this research. In addition to Islam, elements of Hinduism and Buddhism can also be found in these healing rituals, reflecting a form of religious syncretism. The purpose of this study is to explain why the community continues to practice this ritual from the perspective of Surah Al-Baqarah, Verse 165. A qualitative method involving observation and interviews was used to collect data. The findings indicate that the Malay Batubara community performs the ubat-ubat ritual to avoid misfortune and express gratitude to the Creator, who has provided sustenance to His servants through objects and nature. Whether conducted individually or collectively, this ritual reflects the love for Allah, as stated in Surah Al-Baqarah, Verse 165, which serves as the foundation for strengthening the devotion of believers. The author hopes that this religious tradition does not become mystical or negatively impact the community in the future, whether in terms of education, economy, or religion, despite this ceremony being held annually.